SISTEM INFORMASI PENCARIAN GEDUNG PERTEMUAN DI KOTA SEMARANG BERBASIS WEB (Information Technology and Telematics, 2016)
Abstract- Currently seekers building or owner of the building in general is still doing the business transaction manually through direct face to face or over the phone. The difficulty that occurs in this business is the owner of the building where the difficulty in marketing the buildings owned. So also with the search party building difficulty in finding the necessary building. And also the owner of the building is also the difficulty in making a web-based application itself to market the building owned. This research aims to make creating search information system building using PHP and MySQL so that the user can easily search for building online. System development method used is waterfall at the beginning stages of the system, system analysis, system design using UML and implementation of systems using PHP and MySQL.The results in this study was the establishment of information system building searches that can be used by users to search the building and to display details of the building and the location of the building in the form of a map google map. Keywords– Information System, Builiding Search,PHP, MySQL